The impact of monetary policy on private capital formation in Nigeria: Autoregressive Distributed Lag Approach - Olufunke Iyabo Ajoje; Olufemi Samuel Adegboyo; Yetunde Moriliat Aliu (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2022)
The study examines the impact of monetary policy on private capital formation in Nigeria from 1980 to 2020. The study adopts Keynes's theory of capital formation as its theoretical framework. The stationarity tests show a mixed level of stationarity among the variables. Consequently, the study employs ARDL as its estimation technique. The study reveals that Monetary Policy has a positive impact on Private Capital Formation in Nigeria. Based on the findings, the study recommends that the government should maintain the current Monetary Policy Rate (MPR) to continue impacting Private Capital Formation positively. Secondly, the government should formulates appropriate policies that will ensure that the Exchange Rate (EXCHR) is stable so that it can improve the level of Private Capital Formation in Nigeria. Lastly, the government should embark on policies that will curb inflation or help reduce the rate of inflation to increase the level of Private Capital Formation.